Les réactions de la doctrine à la création du droit par les juges en droit international privé - Groffier, Éthel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
Although scholarly writing is still a relatively recent phenomenon in Québec private international law, it has often been strongly critical of judicial decisions which attempt to formulate or reformulate non-codal conflicts rules. Two trends are discernible : the defence of the civilian origin of Québec law against the imposition of common law rules which are not in harmony with the policy of the system ; and the advocacy of a modernization of existing solutions as well as the introduction of techniques and approaches such as material rules and rules of immediate application.